THE CONTROVERSY OF POLITICAL ADVERTISING IN 2017 DKI JAKARTA REGIONAL ELECTION - Ervan Ismail (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
The 2017 DKI regional election which was considered to be on the same level as the Presidential Election implies a need for high capability in its implementation by all relevant stakeholders. The issue of the political contract adver- tisement from the contestants Ahok-Djarot with Djan Faridz’s version of PPP which appeared on television before the campaign period had heated the competition between political parties, the success teams and the 2017 DKI re- gional  election  contestants.  As  there  was  a  complaint  from  Romahurmuziy’s  version  of  PPP  which  supported  the contestants Agus-Sylvi to DKI’s Bawaslu and KPID, this case became a controversy that had been discussed contin- uously in mass media. Thus, it required a solution and regulations’ review on whether the advertisement contained violations on its airing time, its content and messages which can lead to the cancellation of the contestants Ahok- Djarot in the 2017 DKI Regional Election. This study tries to find out the content of the advertising messages from the Djan Faridz’ version of PPP that advertise their political contract to support the contestants Ahok-Djarot in the 2017 DKI DKI Regional Election. The study also aims to find out whether there is a violation and how to handle it. The study type is qualitative descriptive with content analysis method. The elements of that advertisement were in- terpreted and analyzed through the perspective of political  communication and development communication. Fur- thermore, it is analyzed based on the regulatory reviews of  KPU and KPI whether there is a violation. The contro- versy was presented through the news from online media, as well as a literature analysis of why the advertising ap- peared  on  television.  The  results  of  the  study  show  that  the  advertisement  from  Djan  Faridz’  version  of  PPP  is  a form of development communication and also a political advertising which serves to inform the real commitment of the contestants Ahok-Djarot in building a mosque and show them as pro-Muslim leaders. The study concluded that based on the advertising regulation, there is a campaign violation as it contains the elements of program information from the contestants Ahok-Djarot regarding the construction of the mosque and there is also a sign of PPP political party. The advertisement is not placed through KPUD DKI and not in the allowed period time of campaigns through mass media. Bawaslu DKI find it difficult in determining the elements of violation as the campaign advertisement is not placed by the official team and is not recognized as an official activity by the success team of the contestants Ahok-Djarot. KPID DKI then ask TV One and Kompas TV to clarify the advertisement of Djan Faridz's version of PPP while at the same time stopping the advertisement although those two television stations claim that the adver- tisement is an ordinary one. Keywords: Political Advertising, Party Ads, Campaigns, DKI Jakarta Election Keywords: Advocacy, Communication, Social Mobilization